Awareness of Elementary School Teachers about Assessment of Personal-social Qualities of Learners - Mishra, Sudarshan; Moharana, Tapaswini (INDIAN EDUCATIONAL REVIEW, 2019)
The investigators undertook a study related to awareness of teachers about assessment of personal-social qualities (PSQs) of learners in the context of implementation of continuous and comprehensive evaluation (CCE) scheme in Odisha. Descriptive survey method was followed for the present study. A sample of thirty six elementary schools was selected randomly from three districts of Odisha namely, Cuttack, Khordha and Nayagarh. One hundred fifty-five elementary school teachers were selected from these districts. An awareness schedule was developed by the investigators to collect relevant data from the teachers. Results showed that overall awareness of teachers towards assessment of PSQs of the learners in elementary schools was high. No significant difference was found in awareness of teachers about assessment of PSQs of students with reference to gender, locality, qualification and teaching experiences. Based on the findings, possible implications of the study have been discussed.